The Grainsize Analysis of the Estuary of the River Ångermanälven Sediments - Kekäläinen, Pirkko (Helsingfors universitet, 2016)
The sampling was done in 2013 during the Integrated Ocean Drilling Program Expedition 347 on two sites in the river Ångermanälven estuary in Sweden. The area has had the highest rate of uplift in Fennoscandia since the last glaciation. The area was freed from ice 10 500 years before present, after which the shore displacement has been notable. The sedimentation environment has changed considerably from an ice proximal setting, through open sea to a less exposed estuary. The varve deposition is an ongoing process in the estuary since several thousands of years, and it has been correlated to annual discharge, which makes the estuary interesting for palaeoenvironmental studies. The aim of the study was to analyze the changes in the grainsize distribution and to link these changes to the environmental changes. The initial subsampling was made in Bremen in 2014 and the analysis in the laboratory of the Department of Geosciences and Geography of the University of Helsinki in 2015. A method, in compliance to the ISO 13320:2009 standard, was used in the laser diffraction particle size analysis. Also the water content and loss-on-ignition (LOI) was determined from selected samples. The results were processed with the statistics program GRADISTAT 8.0. The resulting figures were compared between the sites and displayed as a function of depth. The sediment consists of varying silt and sand deposits, in which both regular and irregular changes were seen. Interpretations of the sedimentation environments were made and compared with the results of earlier studies. At least three sedimentary units were recognized. Within the upper organic rich silt unit, the point of maximum salinity of the Baltic Sea was recognized. Also the effects of the shoreline displacement, as a coarsening of the sediment, with the decreasing distance to the source of the material, were noted. The unit was interpreted to the brackish Litorina Sea stage. The middle unit was more varied and the relationship between the two sites was more complex. A finer ...